Analisa Dampak Revitalisasi Pasar Tradisional Terhadap Pendapatan Pedagang Pasar (Studi pada Pasar Tradisional Desa Bulubrangsi Kec. Laren Kabupaten Lamongan) - Hartono Hartono; M Adik Rudiyanto; Fachrudy Asj'ari (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to determine the impact of Traditional Market Revitalization on marked trade Revenues (stud at the Traditional Market in Bulubrangsi Village, Laren District, Regency lamongan. The independent variabel sudied was Market Revitalization impact (X). With the dependent variable being Merchant income (Y) at the Traditional Market of the Bulubangsi Village. The population in this study is that all trades of the Bulubrangsi Traditional Market who are regularly selling on the market evry day. The sampling technikue used in this study is Jenu Sampling technique with a total sample of 98 resondents. Based on the results of testing through partial T test Revitalization variable has a significant effect on the income of traditional market trades in the village of Bulubrangsi t count =23,159>t table=0,254 with a signivicant value 0,000<0,05 From these result it can be concluded that Ho is rejected while Ha is acceoted. This shows that the Revitalization carried out in the Bulubrangsi village Tradistional Market is a positive effect on merchant income.